Does the government’s environmental attention improve enterprise green innovation?—Evidence from China - Chen, Jing; Li, Qinyang; Wang, Xiangjun (Frontiers in Environmental Science, 2022)
In recent years, governments worldwide have paid more attention to environmental issues, and green innovation is essential to balance economic growth and environmental sustainability. This paper investigates the different impacts of the government’s environmental attention on green innovation of heavy-polluting and non-heavy-polluting firms using the sample of listed firms in China from 2011 to 2019. We find that the relationship between the government’s environmental attention and green innovation is consistent with the “U”-shape in heavy polluting firms. However, the government’s environmental attention positively impacts the green innovation of non-heavy polluting firms. In addition, fintech mitigates the negative effects of the government’s environmental attention on green innovation in the short term while enhancing the positive effect of the government’s environmental attention on green innovation in the long term for heavily polluting firms. Our paper provides evidence and implications for environmental regulation in developing countries and urban areas.